2009
DOI: 10.3109/14767050903009222
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight, preterm birth and short interpregnancy interval in Sudan

Abstract: In this study, IPI shorter than 18 months are independently associated with increased risk of adverse perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…Their analysis has also been criticized for failing to control for potential confounders that vary by country (such as breastfeeding, which has an impact on postpartum fertility) and which might help to explain the heterogeneity of results (9). Since publication of this systematic review, several investigations of the association of inter‐pregnancy interval and subsequent preterm birth have contributed additional and, in some instances, more refined information about this relation (10–20). Studies that met Conde‐Agudelo and colleagues’ inclusion criteria, but which were published after their review, are summarized in Table 1, along with the key results from the Conde‐Agudelo review for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Their analysis has also been criticized for failing to control for potential confounders that vary by country (such as breastfeeding, which has an impact on postpartum fertility) and which might help to explain the heterogeneity of results (9). Since publication of this systematic review, several investigations of the association of inter‐pregnancy interval and subsequent preterm birth have contributed additional and, in some instances, more refined information about this relation (10–20). Studies that met Conde‐Agudelo and colleagues’ inclusion criteria, but which were published after their review, are summarized in Table 1, along with the key results from the Conde‐Agudelo review for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The result of this study is in corresponding with data reported from other countries in the region such as UAE, Sudan and Qatar. [18][19][20] In Yemen, approximately 54% of population live under the poverty line and survive on fewer than 2 dollars per day, with about two thirds of the population live in rural areas where health care are limited and of poor quality. 21 The importance of maternal education as one of the key determinants for maternal and child health is well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity during pregnancy is a big health problem in Sudan: 19.4% of Sudanese women of any parity are obese, and obesity has been associated with adverse maternal and perinatal outcomes . Short IPI was investigated in a previous study in Sudan, but only in terms of its determinants and outcomes; long IPI or the effect of IPI on obesity was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Ali ET AL study in Sudan, 12 but only in terms of its determinants and outcomes; long IPI or the effect of IPI on obesity was not assessed. Therefore, the aim of the current study was to investigate the determinants of IPI and the effect of IPI on body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters) among pregnant Sudanese women.…”
mentioning
confidence: 99%